2006
DOI: 10.1111/j.1745-7599.2006.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescriptive patterns of nurse practitioners and physicians

Abstract: The results, although statistically significant in only one category, indicate that NPs may be more cautious in their prescriptive interventions and provide more teaching for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…The majority of studies presented self-reported data from providers about their own practice or their perceptions of APRN/PAs practice [24,25,28,31,35,37], while only a few presented self-reported data from patients [32,38]. Few studies reported receipt of services or documented changes in behavior as part of chart reviews [26,27,36,39]. A small number reported any patient characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies presented self-reported data from providers about their own practice or their perceptions of APRN/PAs practice [24,25,28,31,35,37], while only a few presented self-reported data from patients [32,38]. Few studies reported receipt of services or documented changes in behavior as part of chart reviews [26,27,36,39]. A small number reported any patient characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…7 Often, only patients with Unlike many other drugs whose use is generally limited to well-trained specialists (e.g., antipsychotics or chemotherapeutic agents), antimicrobials are prescribed by virtually all doctors and allied healthcare practitioners, regardless of training or knowledge, across a wide spectrum of practice. [8][9][10] To address the development of antimicrobial resistance and to support prescribers in their efforts to treat patients effectively, antimicrobial stewardship programs have been developed worldwide. [11][12][13][14][15][16] Likewise, there are no data on whether medical students believe they receive adequate education on appropriate antimicrobial use, or the degree to which they feel prepared to prescribe these medications appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that nurse practitioners in the US prescribe appropriately and have prescribing patterns similar to those of physicians. 5,6 Using data from the National Ambulatory Medical Care Survey, Hooker and Cipher 5 analyzed 149 202 primary care visits over a six-year period in which a prescription was written by a nurse practitioner, a physician assistant or a physician. The therapeutic classes prescribed and the number of prescriptions written per visit were similar between the three groups.…”
mentioning
confidence: 99%
“…Nurse practitioners tended to prescribe more overthe-counter medications and recommend more nonpharmacologic treatments to patients than physicians did, which suggests that nurse practitioners may approach prescribing more cautiously and include more patient teaching. 6 Evidence shows that patients are satisfied with the care provided by nurse practitioners. Newhouse and colleagues 7 conducted a systematic…”
mentioning
confidence: 99%